Web-search and address distribution of information on the basis of modeling of verbal associations - S. F. Lipnitsky (Informatika)
A mathematical model is proposed for the processes of websites scanning and addressing (selective) distribution of the text information found after the request of users in the form of their information profiles, i. e. accumulated archives of relevant Internet publications. The functional components of such an information system are three subsystems: the subsystem of texts indexing, user archives and short messages; web page scanning subsystem; the subsystem of address distribution of texts and short messages to users. Indexing the texts, archives of users and short messages is reduced to the construction of their verbal-associative networks. The indexing subsystem includes a set of linguistic dictionaries for calculating the informational content of words and verbal-associative links between them. Dictionaries are formed based on the use of publications from user’s archives. Scanning the web pages is carried out on the basis of software solutions in the form of specialized agents, whose main task is to obtain systematically and accumulate new data from updated pages. Scanning is implemented as the sequence determined by a special ordering relationship, which is fixed on the set of web pages of each web site scanned. Distribution of found publications occurs by comparing the verbal-associative networks of these publications and users’ information profiles in the form of search images.